Postsynaptic Hebbian and non-Hebbian long-term potentiation of synaptic efficacy in the entorhinal cortex in slices and in the isolated adult guinea pig brain. - Alonso, A (1990)
Long-term potentiation (LTP) was investigated in the mammalian entorhinal cortex by using two in vitro preparations, the isolated brain and the entorhinal cortex slice. Hebbian and non-Hebbian types of LTP appear to be present in layer II entorhinal cortex cells as demonstrated using two protocols: (i) tetanic stimulation of the piriform-entorhinal cortex afferent pathway to generate homosynaptic potentiation and (ii) postsynaptic subthreshold rhythmic membrane potential manipulation not paired to presynaptic activation, which gives rise to non-Hebbian LTP. The induction and the expression of both types of LTP were found to be dependent on activation of N-methyl-D-aspartate receptors as shown by their sensitivity to the receptor agonist D-2-amino-5-phosphonovalerate. This is in contrast to LTP in the hippocampus [Zalutsky, R. A. & Nicoll, R. A. (1990) Science 248, 1619-1624], where LTP is expressed by quisqualate receptors. Since, in the entorhinal cortex, LTP is linked to a selective increase of the N-methyl-D-aspartate-receptor-mediated synaptic responses, this enhancement is most likely due to postsynaptic factors.